Investigation of the Nanostructure of Crystals by the Method of X-Ray Structural Analysis (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The significance and role of using the method of X-ray diffraction analysis in the study of the nanostructure of crystals are incomparable. By analyzing X-ray images obtained with an X-ray diffractometer, one can obtain sufficient information about the nanostructure of a crystal. Crystal symmetry, crystal lattice parameter, crystallite size, density of dislocations, microstrains, etc. are determined by X-ray diffraction analysis. This article discusses the determination of these structural parameters by X-ray diffraction analysis